2010
DOI: 10.1002/hipo.20847
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin2‐R in medial septum regulate hippocampal and amygdalar ACh release induced by intraseptal application of neurokinins A and B

Abstract: The neurokinin receptors (NK-R), NK(2)- and NK(3)-R, have been implicated in behavioral processes, but apparently in opposite ways: while NK(2)-R agonism disrupts memory and has anxiogenic-like action, NK(3) -R agonists facilitate memory and display anxiolytic-like effects. Systemic application of NK(2)-R antagonists block the release of acetylcholine (ACh) in the hippocampus, which is induced by intraseptal administration of the NK(2)-R ligand, neurokinin A (NKA). We investigated the effects of medial septal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…In the open eld test, anxiolytic-like effect was observed with both low dose (0.2 mg/kg) and high dose (0.4 mg/kg) of senktide [20]. In another study, while NK2R agonism has memory loss and anxiogenic effects, NK3R agonists have been reported to show memory-healing and anxiolytic effects [25]. In our project the distance moved, velocity and movement were found to be reduced in the nal measurement values.…”
Section: Behavioral and Memory Testssupporting
confidence: 48%
See 3 more Smart Citations
“…In the open eld test, anxiolytic-like effect was observed with both low dose (0.2 mg/kg) and high dose (0.4 mg/kg) of senktide [20]. In another study, while NK2R agonism has memory loss and anxiogenic effects, NK3R agonists have been reported to show memory-healing and anxiolytic effects [25]. In our project the distance moved, velocity and movement were found to be reduced in the nal measurement values.…”
Section: Behavioral and Memory Testssupporting
confidence: 48%
“…Control animals were injected with solvent. Doses were determined taking into account previous studies that showed a healing effect in learning and memory tests [20,21,25,26,27,28].…”
Section: Drug Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…NK2R and NK3R, which modulate their excitability (Chen et al, 2001;de Souza Silva et al, 2013;Morozova et al, 2008;Schäble et al, 2012;Steinberg et al, 1998). Indeed, the NKR are almost exclusively localized to septal cholinergic neurons.…”
Section: Introductionmentioning
confidence: 99%